PENGARUH PARAMETER KECEPATAN POTONG TERHADAP EFISIENSI MESIN PENGIRIS UBI KAYU - Fahrizal; Sealtial Mau; Priyono; Edy Suprapto; Basri K; Wofrid Bianome, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Producing cassava slices with minimal damage is an important goal in the chips making process. The lower level of damage, the higher efficiency of the slicing results. The level of efficiency is influenced by a number of parameters including cutting speed. However, information about the influence of these factors is not yet widely available. The aim of this study is to determine the effect of cutting speed on slicing efficiency and obtain the highest level value to produce maximum efficiency. This research used a completely randomized design. In this technique, the factor was cutting speed with four levels, namely 323 rpm, 392 rpm, 485 rpm and 595 rpm. The experiments were replicated ten times. Data collection was carried out by directly measuring the efficiency of each treatment. Analysis of variance was used to determine whether there was a significant difference between cutting speed and slicing efficiency. Normality and homogeneity of variance tests were carried out as analysis requirements. Duncan's test was carried out to see the effect between treatments. The results concluded that the slicing efficiency measurement data was normally distributed and homogeneous. There was a significant difference between cutting speed and slicing efficiency. Maximum slicing efficiency was obtained at 485 rpm.